Analisis Semiotika Poster Film Horor KKN di Desa Penari - Isma Rahmadani; Nabila Nur Atikah; Dwi Aji Pratama; Maulana Andinata Dalimunthe; Hasan Sazali (Professional: Jurnal Komunikasi dan Administrasi Publik, 2022)
Movie posters play an important role in the promotion process of a film. Therefore, to convey the message well, film posters are made as good as possible by presenting unique and interesting poster visualizations. The KKN di Desa Penari film poster is one of the poster art works that is able to focus on visual signs, such as visuals of dancers, cultural elements, and the characteristics of design elements such as colors, layouts, images, logos, and typography. This study aims to determine the meaning of the signs contained in the KKN di Desa Penari film poster. The data sources in this study were divided into two, namely primary data (KKN di Desa Penari film posters) and secondary data (documents, articles, and online sites). Then, the data is translated into language so as to produce information related to the research objectives. This study uses Charles Sanders Peirce's semiotic theory which includes icons, indexes, and symbols in the interpretation stage. The results of this study indicate that the KKN di Desa Penari poster shows something different by presenting a stealth visual with a beautiful form than a ghost figure which is known to be scary. Furthermore, the KKN di Desa Penari film poster also contains cultural elements so that it creates a strong traditional impression.